Inhibitory Effects of the Edible Mushroom Flammulina velutipes on Lipid Accumulation in 3T3-L1 Cells - Yasuhito Nobushi; Yuki Hamada; Ken Yasukawa (Journal of Pharmacy and Nutrition Sciences, 2013)
We investigated the inhibitory effect of the edible mushroom Flammulina velutipes on intracellular lipid accumulation. Among the five fractions of the F. velutipes extract, the acetone fraction had an inhibitory effect on intracellular lipid accumulation. Seven known compounds were isolated from the acetone fraction: methyl linoleate, methyl γ-linolenate, ergosterol, ergosta-5,7-dien-3β-ol, ergost-7-en-3β-ol, ergosterol peroxide, and 5,6-epoxy-24(R)-methylcholesta-7,22-dien-3β-ol. Ergosterol peroxide exhibited a potent inhibitory effect on the intracellular lipid accumulation. Our results indicate that ergosterol peroxide may be important as an anti-obesity agent since it inhibits the metabolic syndrome.